Detection of FMS-like Tyrosine Kinase 3 (FLT3) and Nucleophosmin 1 (NPM1) mutations from marrow tissues in patients with Acute Myeloid Leukaemia - Mansoor, Muhammad Naeem; Muhammad, Naznin; A. Talib, Norlelawati; Ismail, Rusmawati; Ibrahim, Ismail; Abdul Aziz, Karimah Hanim; Hamdan, Asmah Hanim (International Islamic University Malaysia, 2022)
INTRODUCTION: Acute myeloid leukaemia is a haematological malignancy with diverse cytogenetic abnormalities and molecular mutations. Amongst the important mutations are FMS-related tyrosine kinase 3 (FLT3) and nucleophosmin 1 (NPM1) gene mutations. These mutations have been shown to be of prognostic significance. A cross-sectional study to examine the frequency of these mutations and their association with the haematological and cytogenetic characteristics of the cases was carried out in Kuantan, Pahang, Malaysia. MATERIALS AND METHODS: A total of 43 cases were included in the study. Polymerase chain reaction-based assays were employed for mutation detection from the retrieved trephine biopsy tissue blocks. Mutation positivity was subsequently validated by Sanger DNA sequencing. RESULTS: Six of the 43 cases (14.0%) of the acute myeloid leukaemia were positive for FLT3-type internal tandem duplications (FLT3- ITD) and a similar proportion (6/43, 14.0%) were positive for NPM1 mutations. FLT3 mutations at codon D835 (FLT3-D835) mutation was identified in three of the cases (7.0%) while concurrent mutations of NPM1 and FLT3-ITD were seen in two of the mutation-positive cases (4.7%). The total white cell count was found to be significantly higher in patients with FLT3 mutations (p=0.001). Other haematological parameters and the cytogenetic results did not reveal any significant association with the mutational status. CONCLUSION: The frequency of FLT3-ITD, FLT3-D835, and NPM1 mutations among AML patients were 14%, 7%, and 14% respectively. Follow-up studies to include the clinical parameters and the treatment outcomes are advocated.